(untitled) (Applied Biological Research, 2023)
Protein A/G (pA/G) has high affinity with the fragment crystallizable (Fc) region of antibodies so is used as a linker to attach antibodies to quantum dots (QDs), thereby helps the antigen-binding fragment (Fab) to expose outwardly. The present study deduced the interactive nature between pA/G and mercaptosuccinic acid-coated CdSe (CdSe/MSA) QDs by using different reagents to interfere the binding formation. Besides, the use of pA/G-conjugated QDs (QDs-pA/G) in Western blot was tested by using QDs-pA/G associated with anti-GST antibodies to label mPrPc-GST protein in Escherichia coli lysates. The results showed that most of the pA/G could not bind to QDs in presence of 2% sodium dodecyl sulfate, 0.1 ol and 1% tween 20. The study revealed that pA/G was mostly bound to CdSe/MSA QDs by non-covalent interactions. The QDs pA/G wassuccessfully applied in direct Western blot with a stronger signal